SOME ISSUES OF THE APPLICATION OF NORMS DETERMINING RESPONSIBILITY FOR TERRORIST FINANCING (European Journal of Economics, Finance and Business Development, 2025)
Financing terrorism is a preeminent international issue with profoundly disturbing consequences for national and international security. The current article examines the norms and paradigms of regulating the obligation of terrorist financing, emphasizing the obstacles to putting these rules into meaningful effect. Enforcement difficulties are caused by critical legal subtleties, jurisdictional differences, and evolving terrorist financing means. Drawing on an analysis of some legislative measures and case studies, this article attempts to identify major gaps and recommend ways of enhancing the effectiveness of efforts to counter-terrorist financing.